Mesenteric fat proliferation on magnetic resonance enterography is a predictor of long-term disease complications in crohn’s disease - Eduard Koifman; Inna Spector Cohen; Rebeca Lopez-Alonso; Dana Ben Hur; Anat Ilivitzki; Matti Waterman (BMC Gastroenterology)
Abstract Background Fibrofatty proliferation of mesenteric fat is a common finding on magnetic resonance enterography (MRE) in Crohn’s disease (CD) patients. Mesenteric fat may play a role in inflammation, fibrosis, and stricture formation, but its prognostic value in predicting complications remains unclear. Objectives To assess the association between mesenteric fat proliferation on MRE and the risk of hospital admissions and bowel surgery in CD patients. Methods In this retrospective single-center study, CD patients with available MRE data were followed for CD exacerbation-related hospitalizations or abdominal surgeries. An expert radiologist reviewed MRE for intestinal wall thickening, stricture, abscess formation, fibrofatty proliferation, and fat edema. Kaplan-Meier and Cox proportional hazards regression models were used to analyze associations between mesenteric fat and outcomes, adjusting for clinical and imaging characteristics. Results Among 175 CD patients mesenteric fat proliferation and edema were noted in 52 (29.7%) and 15 (8.9%) patients, respectively. Other findings included wall thickening (46.9% mild, 29.1% moderate, 7.4% severe), stricture (14.3%), abscess (5.7%), and fistula (6.9%). During a mean follow-up of 95.2 months, 93 (51.3%) patients were hospitalized for CD-related reasons, and 47 (26.9%) underwent CD-related abdominal surgery. Mesenteric fat proliferation was strongly associated with hospitalizations and surgery (p < 0.0001 for both). Multivariable analysis confirmed these associations with adjusted hazard ratios (aHR) of 3.45 (95%CI 1.66–7.19) 3.74 (95%CI) for surgery and 1.92 (95%CI 1.16–3.15) 2.03 (95%CI) for hospitalizations. Fat edema was linked to surgery and hospitalization but lost significance in multivariable analysis. Conclusions Mesenteric fat proliferation on MRE is independently associated with increased risk of hospitalizations and surgery in CD patients.